Note on Szász–Mirakyan–Durrmeyer Operators Preserving e2ax, a>0. (25th January 2018) - Deniz, Emre; Aral, Ali; Gupta, Vijay
ABSTRACT: In the current article, we study Szász–Mirakyan–Durrmeyer operators which reproduces constant and e 2 ax, a >0 functions. We discuss a uniform estimate and estimate a quantitative asymptotic formula for the modified operators.